Practical design of power supplies. - Lenk, Ron, ....- (Hoboken : Wiley, 2005)
Practical Design of Power Supplies details key techniques and offers advice to engineers and technicians who want to design and build power supplies that work the first time they are turned on. Leading authority Ron Lenk presents current, experiment-based information that can save hours of research and design time. Containing many handy "Practice Notes" and real-world examples, Practical Design of Power Supplies is an excellent how-to reference to keep by your side throughout the design, lab, and production phases. The topics covered will be immediately useful in everyday circuits and systems work: * Common terms and instrumentation * How to design successful magnetics * How to compensate the feedback loop to obtain stable operation * Practical EMI * Topology selection * Worst-case analysis Practical Design of Power Supplies will be especially useful to designers who need to understand and implement the concepts behind loop compensation and magnetics design.